Pengaruh Harga dan Kualitas Produk Terhadap Keputusan Pembelian Frozen Sirsak: Pengaruh Harga dan Kualitas Produk Terhadap Keputusan Pembelian Frozen Sirsak - Yuan Alfian; Navita Maharani; Vifi Nurul Choirina (JURNAL ILMIAH AGRINECA, 2026)
The perishability of soursop fruit necessitates value-added processing innovations to minimize post-harvest losses and improve market competitiveness. Frozen soursop products represent one such innovation; however, consumer purchasing decisions are influenced by perceptions of price and product quality. This study aimed to examine the effects of price and product quality on purchasing decisions for frozen soursop products in Wonorejo Trisulo Village, Kediri Regency. A quantitative approach was employed using purposive sampling involving 105 consumers who had previously purchased frozen soursop products. Primary data were collected through Likert-scale questionnaires and analyzed using multiple linear regression. The findings revealed that price and product quality had positive effects on consumer purchasing decisions, both partially and simultaneously. Product quality was identified as the most influential factor affecting purchasing behavior. These findings highlight the importance of maintaining product quality while implementing appropriate pricing strategies to enhance consumer interest and competitiveness of frozen soursop products. This study provides practical implications for agroindustry stakeholders in developing value-added products from perishable agricultural commodities.